Labor Protection for Occupational Safety in Construction Companies - Dwi Atmoko; Noviriska Noviriska; Jantarda Mauli Hutagalung (Asosiasi Dosen Muda Indonesia, 2026)
Currently, many people work in the construction sector, whether they work independently or collaboratively, regarding protection in employment relationships, or working for others for their services. This research uses a normative legal approach coupled with a phenomenon-based approach. Obstacles and efforts include a lack of awareness of the importance of worker health and safety in the workplace, and a lack of compliance with company-provided safety regulations. Efforts must be made by construction companies that handle high-rise buildings, which have high risk factors, requiring maximum occupational safety and health protection and ensuring worker safety. The company's good faith in providing occupational safety and health facilities is crucial in the work activities of a construction project. Provision of safety facilities and infrastructure is necessary to prevent workplace accidents. Furthermore, training and knowledge of occupational accidents and risks must be frequently addressed to reduce the rate of workplace accidents in the construction sector.